Sulla revocatio in servitutem dei liberti ingrati in alcuni rescritti tardoclassici - Schiavo, Silvia (Tesserae iuris, 2023)
The article deals with ingratitude of freedmen and with revocatio in servitutem of liberti ingrati. The author tries to demonstrate that from a group of late classical rescripts it is possible to see clues of its existence and application, despite a widespread scholar opinion, according to which the same constitutions would forbidden this sanction.